2018
DOI: 10.2147/cmar.s176317
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic impact of lactic dehydrogenase to albumin ratio in hepatocellular carcinoma patients with Child–Pugh I who underwent curative resection: a prognostic nomogram study

Abstract: BackgroundRadical resection is the treatment of choice for hepatocellular carcinoma (HCC). However, even with this treatment, HCC prognosis and the efficacy of current predictive models for such patients remain unsatisfactory. Here, we describe an accurate and easy-to-use prognostic index for patients with HCC who have undergone curative resection.MethodsThe study population comprised of 1,041 patients with HCC who underwent curative resection at Zhongshan Hospital. This population was reduced to 768 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Studies have shown that malnutrition often leads to poor tumor prognosis ( 24 ). In studying the HCC clinical nomogram model, albumin-based nutritional indexes, including the albumin-bilirubin grade and lactic dehydrogenase/albumin ratio, showed good prognostic predictive performance ( 25 , 26 ). In this study, we explored the albumin-based PNI.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that malnutrition often leads to poor tumor prognosis ( 24 ). In studying the HCC clinical nomogram model, albumin-based nutritional indexes, including the albumin-bilirubin grade and lactic dehydrogenase/albumin ratio, showed good prognostic predictive performance ( 25 , 26 ). In this study, we explored the albumin-based PNI.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Gan et al . [ 14 ] found that increased LAR levels were associated with a poor prognosis in patients with hepatocellular cancer. In both of these studies, the cutoff value for LAR was determined as 5.5.…”
Section: Discussionmentioning
confidence: 99%
“…The LDH-to-albumin ratio (LAR) is a prognostic tool used in cancer patients. Elevated LAR levels have been associated with poor prognosis in esophageal and hepatocellular cancers [ 13 , 14 ]. Nevertheless, to our knowledge, there are a limited number of studies reporting on the prognostic value of LAR, and there has been no study specifically reporting on the effect of LAR on prognosis in patients with gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…With a high LDH-to-albumin ratio, survival is expected to be poor. Although there is little or no documentation of the LDH-to-albumin ratio in the literature, LDH-to-albumin ratio has been shown to be associated with a poor prognosis in esophageal and hepatocellular cancers [ 20 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors determined a cutoff value of 5.5 for LDH-to-albumin ratio and suggested that LDH and albumin alone had no effect on the prognosis of the disease [20]. In another study, Gan et al [21] found that high LDH-to-albumin ratio was associated with poor prognosis in patients with hepatocellular cancer. The drawback of that study is that both LDH and albumin levels could be affected by the presence of the underlying chronic liver disease regardless of the tumor.…”
mentioning
confidence: 99%